Base excision of oxidative purine and pyrimidine DNA damage in Saccharomyces cerevisiae by a DNA glycosylase with sequence similarity to endonuclease III from Escherichia coli. - Eide, L (1996)
One gene locus on chromosome I in Saccharomyces cerevisiae encodes a protein (YAB5_YEAST; accession no. P31378) with local sequence similarity to the DNA repair glycosylase endonuclease III from Escherichia coli. We have analyzed the function of this gene, now assigned NTG1 (endonuclease three-like glycosylase 1), by cloning, mutant analysis, and gene expression in E. coli. Targeted gene disruption of NTG1 produces a mutant that is sensitive to H2O2 and menadione, indicating that NTG1 is required for repair of oxidative DNA damage in vivo. Northern blot analysis and expression studies of a NTG1-lacZ gene fusion showed that NTG1 is induced by cell exposure to different DNA damaging agents, particularly menadione, and hence belongs to the DNA damage-inducible regulon in S. cerevisiae. When expressed in E. coli, the NTG1 gene product cleaves plasmid DNA damaged by osmium tetroxide, thus, indicating specificity for thymine glycols in DNA similarly as is the case for EndoIII. However, NTG1 also releases formamidopyrimidines from DNA with high efficiency and, hence, represents a glycosylase with a novel range of substrate recognition. Sequences similar to NTG1 from other eukaryotes, including Caenorhabditis elegans, Schizosaccharomyces pombe, and mammals, have recently been entered in the GenBank suggesting the universal presence of NTG1-like genes in higher organisms. S. cerevisiae NTG1 does not have the [4Fe-4S] cluster DNA binding domain characteristic of the other members of this family.